Systemic Sympathoexcitation Was Associated with Paraventricular Hypothalamic Phosphorylation of Synaptic CaMKIIα and MAPK/ErK - Ogundele, Olalekan M.; Rosa, Fernando A.; Dharmakumar, Rohan; Lee, Charles C.; Francis, Joseph (Frontiers in Neuroscience, 2017)
Systemic administration of adrenergic agonist (Isoproterenol; ISOP) is known to facilitate cardiovascular changes associated with heart failure through an upregulation of cardiac toll-like receptor 4 (TLR4). Furthermore, previous studies have shown that cardiac tissue-specific deletion of TLR4 protects the heart against such damage. Since the autonomic regulation of systemic cardiovascular function originates from pre-autonomic sympathetic centers in the brain, it is unclear how a systemically driven sympathetic change may affect the pre-autonomic paraventricular hypothalamic nuclei (PVN) TLR4 expression. Here, we examined how change in PVN TLR4 was associated with alterations in the neurochemical cytoarchitecture of the PVN in systemic adrenergic activation. After 48h of intraperitoneal 150mg/kg ISOP treatment, there was a change in PVN CaMKIIα and MAPK/ErK expression, and an increase in TLR4 in expression. This was seen as an increase in p-MAPK/ErK, and a decrease in synaptic CaMKIIα expression in the PVN (p<0.01) in the PVN. Furthermore, there was an upregulation of vesicular glutamate transporter (VGLUT 2; p<0.01) and a decreased expression of GABA in the PVN of Isoproterenol (ISOP) treated WT mice (p<0.01). However, after a PVN-specific knockdown of TLR4, the effect of systemic administration of ISOP was attenuated, as indicated by a decrease in p-MAPK/ErK (p<0.01) and upregulation of CaMKIIα (p<0.05). Additionally, loss of inhibitory function was averted while VGLUT2 expression decreased when compared with the ISOP treated wild type mice and the control. Taken together, the outcome of this study systemic adrenergic activation may alter the expression, and phosphorylation of preautonomic MAPK/ErK and CaMKIIα downstream of TLR4. As such, by outlining the roles of these kinases in synaptic changes, we have identified the significance of neural TLR4 in the progression, and attenuation of synaptic effects in the pre-autonomic sympathetic centers.